Adaptive User Interfaces for Software Supporting Chronic Disease - Wang, Wei; Khalajzadeh, Hourieh; Grundy, John; Madugalla, Anuradha; Obie, Humphrey O. (IEEE/ACM International Conference on Software Engineering: Software Engineering in Society (Online), 2024)
mHealth interventions hold promise for supporting the self-management of chronic diseases, yet their limited utilisation remains a problem. Given the significant variability among individuals with chronic diseases, tailored approaches are imperative. Adaptive User Interfaces (AUIs) may help to address the diverse and evolving needs of this demographic. To investigate this approach, we developed an AUI prototype informed by existing literature and used it as the basis for a focus group and interview study involving 22 participants. Concurrently, a quantitative survey was carried out to extract preferences for AUIs in chronic disease related applications with 90 participants. Our findings reveal that user engagement with AUIs is influenced by individual capabilities and disease severity. Additionally, we explore user preferences for AUIs, expanding the adaptation literature by uncovering usage challenges, proposing practical strategies for enhanced AUI design, and acknowledging potential trade-offs between usability and adaptation. Lastly, we present design considerations for AUIs in chronic disease applications, aiming to prevent user overload and maintain critical software functionality and usability aspects.CCS CONCEPTS* Human-centered computing → Graphical user interfaces; User interface programming.LAY ABSTRACTAlmost half of Australians are estimated to have one or more chronic diseases in 2020-21. Mobile health tools show promise in helping people manage chronic diseases, but these are not commonly used among many individuals with chronic conditions. People with chronic diseases have diverse needs, so a one-size-fits-all approach does not work well. Adaptive User Interfaces (AUIs) offer a solution by tailoring the user experience to individual needs. In our study, we created an AUI prototype based on our investigation of the existing research. We tested our prototype through focus group sessions and interviews. At the same time, we conducted a survey to learn more about their preferences for AUIs in apps related to chronic diseases. Our research revealed that how much users engage with AUIs depends on their individual abilities and the seriousness of their illness. We also discovered what users like and dislike about AUIs, highlighting some challenges in their use. To make AUIs better, we suggested some practical ideas and recognised that there can be a balance between making them easy to use and adaptive. Lastly, we provided some tips for designing AUIs in apps for chronic diseases to ensure they are user-friendly, without making them too complicated, and still offering important features.